Rational design, and synthesis of imidazole ring incorporated Pyridine-1,2,4-oxadiazole derivatives: In-vitro anticancer evaluation and in-silico molecular docking simulations - Rambabu Vasamsetti; Naresh Babu Gatchakayala; Nekuri Bujjibabu; Vudi Sanjeeva Kumar; Tirri Veera Venkata Satyanarayana; Gundu Pavani; Ravi Kumar Kapavarapu; Bandaru Madhav (Results in Chemistry)
We have design and developed a new library of imidazole ring incorporated pyridine-1,2,4-oxadiazole compounds (10a-j) and evaluated for their anticancer activities against a panel of four human cancer cell lines including PC3 & DU-145 (prostate cancer), A549 (lung cancer) and MCF-7 (breast cancer) by using of MTT assay with standard reference as etoposide. The IC50 values of compounds ranges from 0.02 ± 0.0047 μM to 10.3 ± 5.68 μM and the etoposide showed values ranges from 1.97 ± 0.45 μM to 3.08 ± 0.135 μM, respectively. Among all, compounds 10a, 10b, 10c, 10 h, 10i and 10j were displayed more potent activities. The compound 10a with 3,4,5-trimethoxy group on the aryl ring attached to imidazole core moiety exhibited most promising activity (PC3 = 0.17 ± 0.085 μM; A549 = 0.02 ± 0.0047 μM; MCF-7 = 0.07 ± 0.0026 μM & DU-145 = 1.56 ± 0.74 μM). Compounds 10a, 10b, 10c, 10 h, and 10j, featuring methoxy, tolyl, and cyano groups, show strong binding affinities in docking simulations with Human Topoisomerase IIβ, EGFR, and VEGFR2, along with encouraging in vitro results, positioning them as potential lead candidates for anticancer development.